„So it really is a series of tubes." Google’s data centers, noo-politics and the architecture of hegemony in cyberspace - Pearce, Thomas (Enquiry The ARCC Journal for Architectural Research, 2013)
In recent years, the physical manifestation and infrastructure of the informational age has increasingly drawn the attention both of the popular imagination and of architectural theorists. This paper focuses on an aspect mostly overlooked to date, namely on its artistic representation. It provides a critical analysis of a series of data center photographs published by Google in October 2012 under the name "Where the internet lives”. The photographs are examined as carefully staged constructions of a specific imagination of information technology that, transcending a purely aesthetical or corporate critique, has broad political, socio-geographical and economical implications. A first analysis of their composition, digital manipulation and visual impact situates the images within a recent photographic current of the so called "anthropogenic Sublime”. The paper then zooms out to reframe the photographs as a continuation of the euphoric techno-utopian discourse that surrounded the popular dissemination of the internet in the early nineteen-nineties. This discourse hailed the internet as an inherently moral and emancipatory vehicle that, because of the non-physical nature of cyberspace, would liberate its users from traditional hegemonic dispositifs based on techniques of physical coercion. Tracing the transition from bio-political (Foucault) to noo-political dispositifs (Lazarrato, Deleuze) and discussing the inextricable connection between information technology, territorial conflict and socio-geographic inequality, the article goes on to account for the demise of the dream of a "bodiless and moral internet”. Finally, the data center images are re-read in more detail and discussed as part of the life-support system of a failed utopia - sustaining a popular yet reductionist understanding of the informational society and its key players.